Hematology, blood gases and biochemistry profiles of wild-nesting sea turtles in Terengganu, Malaysia - Syamsyahidah Samsol,; Mohd Effendy Abd Wahid,; Tsung, Hsien Li; Mohd Uzair Rusli, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Chelonia mydas is an endangered marine species globally, which its reference blood parameters intervals have been published for some group populations, but baseline health status values are lacking from Malaysia. This study aims to better understand the hematology, biochemical, and blood gas of a wild-nesting green turtle population in the South China Sea. The health status of nesting turtles at the Chagar Hutang Turtle Sanctuary, Pulau Redang, were performed on different individuals, (26 females laid one nest and 2 females laid two nests). A portable handheld blood analyzer (iSTAT) used in the field to obtain immediate results of pH, lactate, pO2, pCO2, HCO3 - , Hct, Hb, Na, K, iCa, and glucose levels in blood samples, while standard laboratory hematology techniques were conducted at Universiti Malaysia Terengganu (UMT) for red and white blood cell counts. The results for all blood analytes (except Na, iCa, and hematology values) were not within the healthy index range for wild turtles, compared to previous studies from different geographic populations. Therefore, the results of this current study help to develop a baseline profile of healthy wild-nesting turtles as a global reference for detecting abnormalities in blood chemistry and the health status of turtle populations worldwide.